STRUKTUR KEPEMILIKAN DAN FINANCIAL DISTRESS: STUDI PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Munandari, Dhealelia; Suryana, Putu Ayu Indira Savitri (Universitas Ahmad Dahlan, 2021)
The purpose of this study was to determine the effect of institutional ownership, insider ownership, government ownership and foreign ownership on the likelihood of companies experiencing financial distress. The sample used is 20 food and beverages companies listed on the Indonesia Stock Exchange for the 2017 - 2019 period. The research method used is using logistic regression analysis. Foreign ownership has a significant influence on the likelihood of financial distress. Meanwhile, institutional ownership, insider ownership and government ownership do not have a significant effect on the likelihood of financial distress in this study.This study aims to determine the effect of institutional ownership, insiderownership, government ownership and foreign ownership on the likelihoodof companies experiencing financial distress. The sample used is 20 foodand beverages companies listed on the Indonesia Stock Exchange for the2017 - 2019 period. The research method used is using logistic regressionanalysis. Foreign ownership has a significant influence on the likelihood offinancial distress. Meanwhile, institutional ownership, insider ownership andgovernment ownership do not have a significant effect on the likelihood offinancial distress in this study.